Anti-browning methods on fresh-cut fruits and fruit juice: A Review - Afoakwah, A. N. (African Science Publications, 2020)
Enzymatic browning is an economically important disorder that degrades the sensory characteristics, and prevent consumer from purchasing fresh-cut fruits and vegetables. Prevention and control of enzymatic browning in fresh-cut fruit products is imperative. This has led to extensive studies being conducted and many methodologies being explored with positive outcomes. However, concerns over off-odors, safety of food, has resulted in few browning inhibitors showing the potential for usage in the fresh-cut fruit-industry. A significant goal has been the discovery of natural compounds with health benefits, which has the potential to provide safe and effective control of enzymatic browning in fresh-cut fruits. Studies on effective combinations of diverse treatments reviewed shows that it has the potential to effectively elongate the shelf-life of fresh-cut fruits while inhibiting the activities of polyphenol oxidase (PPO), thereby maintain product quality and safety.
Keywords: Fresh-cut fruits, Fruit-industry, Enzymatic browning, Polyphenol oxidase activity, Off-odors, Sensory characteristics